2020
DOI: 10.1111/nep.13702
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cumulative fluid balance on acute kidney injury and patient outcomes after orthotopic liver transplantation: A retrospective cohort study

Abstract: AimAcute kidney injury (AKI) is a serious complication following orthotopic liver transplantation (OLT) and it affects long‐term patient survival. The aims of this study were to identify the effects of cumulative fluid balance (FB) on early post‐OLT AKI and adverse outcomes and to construct a model to predict AKI.MethodsWe retrospectively analysed 146 adult patients who underwent OLT. AKI severity was classified according to the Kidney Disease: Improving Global Outcomes (KDIGO) criteria. Univariate and multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
3
8
0
2
Order By: Relevance
“…Patients with sepsis and mechanical ventilation at ICU admission had an increased risk for developing AKI, which has been previously reported in critically ill patients 1,2 . In our patients, albumin level before surgery showed a protective effect for developing AKI, this finding is consistent with previous reports in different types of surgery 25,26,27 …”
Section: Discussionsupporting
confidence: 92%
“…Patients with sepsis and mechanical ventilation at ICU admission had an increased risk for developing AKI, which has been previously reported in critically ill patients 1,2 . In our patients, albumin level before surgery showed a protective effect for developing AKI, this finding is consistent with previous reports in different types of surgery 25,26,27 …”
Section: Discussionsupporting
confidence: 92%
“…Not surprisingly, these four studies confirm what physiology tells us: to achieve a predefined hemodynamic target, a smaller volume of colloid solution, namely HES 130/0.4, is required, compared to crystalloid solution, resulting in a less positive intraoperative fluid balance. Of note, several studies have reported an association between positive perioperative fluid balance and worse outcome [77][78][79][80]. However, among the four studies cited above, our study reported a reduced incidence of postoperative complications with the use of HES solution, associated with a lower intraoperative fluid balance [57].…”
Section: Yesmentioning
confidence: 41%
“…In this study, preoperative serum albumin was not an independent predictor, while preoperative prealbumin showed a strong ability to predict the risk of postoperative complications. Although preoperative albumin is a widely used indicator to evaluate nutritional status and liver function [ 20 , 21 ], a moderate positive correlation with preoperative prealbumin was also exhibited in scatter plots based on Spearman correlation analysis (R = 0.703, P < 0.001). A remarkable finding was that patients frequently received peripheral supplemental infusion of albumin solution due to continuous deterioration of nutritional status and ascites.…”
Section: Discussionmentioning
confidence: 99%